Full-Scale Test to Failure of a Prestressed Concrete Bridge in Kiruna - Bagge, Niklas; Blanksvärd, Thomas; Sas, Gabriel; Bernspång, Lars; Täljsten, Björn; Carolin, Anders; Elfgren, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2014)
To calibrate methods for condition assessment of prestressed concrete (PC) bridges, tests areplanned for a 50 year old five-span bridge with a length of 121 m in Kiruna in northern Sweden.Both non-destructive and destructive full-scale tests will be performed. This paper summarisesthe test programme, which comprises evaluation of the structural behaviour of the bridge, theresidual forces in the prestressed steel, methods for strengthening using carbon fibre reinforcedpolymers (CFRP) and the shear resistance of the bridge slab. Godkänd; 2014; 20140829 (nikbag); Konferensartikel i tidskrift